The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1111/1469-8986.3540372
|View full text |Cite
|
Sign up to set email alerts
|

Frontal brain asymmetry and affective style: A conceptual replication

Abstract: Recent studies have demonstrated that positive and negative affective reactivity can be predicted by resting electroencephalographic (EEG) asymmetry in frontal brain regions. These studies used different methods to assess asymmetry and affectivity. The goal of the present study was a conceptual replication of these results and to investigate their independence of employed procedures. Resting EEG of 37 subjects was recorded and affective slides were presented to obtain ratings of subjects' emotional reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(44 citation statements)
references
References 57 publications
0
42
0
Order By: Relevance
“…Higher asymmetry scores indicate greater relative left frontal activity. before, many researchers currently favor a motivational model of EEG asymmetry over the valence model (see Davidson, 1992Davidson, , 1995Davidson, , 1998Hagemann et al, 1998Hagemann et al, , 1999Debener et al, 2001). The motivational model would predict greater relative right frontal activity during the aversive slide condition only if the participants were motivated to withdraw or engage in withdrawal related behavior while viewing the aversive slides.…”
Section: Discussionmentioning
confidence: 99%
“…Higher asymmetry scores indicate greater relative left frontal activity. before, many researchers currently favor a motivational model of EEG asymmetry over the valence model (see Davidson, 1992Davidson, , 1995Davidson, , 1998Hagemann et al, 1998Hagemann et al, , 1999Debener et al, 2001). The motivational model would predict greater relative right frontal activity during the aversive slide condition only if the participants were motivated to withdraw or engage in withdrawal related behavior while viewing the aversive slides.…”
Section: Discussionmentioning
confidence: 99%
“…Cz was reference and the left earlobe was grounded. We are aware that use of the Cz reference is controversial (Reid et al, 1998;Haggemann et al, 1998;Davidson, 1998). We use it here as it is the reference initially used by the Davidson group to demonstrate correlation of frontal EEG asymmetry and affect, and which we too have used in obtaining the best diagnostic and clinical effects (Rosenfeld, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies showed at least good internal consistency (Cronbach's alpha of about 0.80 and above) with resting EEG recorded for 4 min or more (Reid et al, 1998;Hagemann et al, 1998). However, although a variety of studies assessed cortical asymmetries during experimental manipulations via film clips to alter emotional or motivational responding, to our knowledge the reliability of these EEG recordings has not yet been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of different reference schemes on measurements of frontal trait asymmetry have been in the focus of evaluation before (Hagemann et al, 1998(Hagemann et al, , 2001Reid et al, 1998). Critically, measurements against the most often used mathematically linked ears/mastoids and common vertex references did not show strong associations.…”
Section: Introductionmentioning
confidence: 99%